Gender Determines Pneumonia Risk Factor Patterns in Toddlers in South Kalimantan, Banjar Regency, Indonesia - Leka Lutpiatina; Lilis Sulistyorini; Tini Elyn Herlina; Ahmad Muhlisin (Baiman Bauntung Batuah Center, 2026)
Pneumonia remains one of the leading causes of mortality among children under five worldwide. Previous studies have reported inconsistent findings regarding sex differences in pneumonia susceptibility, suggesting that risk factors may differ between male and female toddlers. This study aimed to identify and compare sex-specific risk factors for pneumonia among toddlers in Banjar Regency, Indonesia. This case–control study included 300 toddlers: 169 male toddlers (61 cases and 108 controls) and 131 female toddlers (45 cases and 86 controls). We assessed 41 demographic, socioeconomic, behavioural, child-related, environmental, and housing indicators through interviews and direct household measurements. We analysed male and female datasets separately. Candidate variables with p<0.25 in simple logistic regression were entered into multivariable logistic regression using the backward stepwise method to identify independent predictors of pneumonia. Among male toddlers, four independent risk factors were identified: stunted child development (OR=7.022; 95% CI: 1.680–29.345), low family income (<minimum wage) (OR=3.305; 95% CI: 1.328–8.228), living within 15 m of the riverbank (OR=2.830; 95% CI: 1.336–5.994), and age 12–59 months (OR=2.236; 95% CI: 1.025–4.878). Among female toddlers, three independent predictors were identified: low family income (OR=3.211; 95% CI: 1.077–9.571), predominant infant formula feeding (OR=2.748; 95% CI: 1.040–7.261), and inadequate household occupancy density (OR=2.641; 95% CI: 1.187–5.876). The findings demonstrate distinct sex-specific risk factor patterns for pneumonia among toddlers. These results suggest that pneumonia prevention strategies should incorporate gender-specific approaches, with greater emphasis on improving child development and environmental conditions for boys, and promoting breastfeeding and adequate housing conditions for girls.